Congenital Pulmonary Airway Malformations With a Reconsideration and Current Perspective on the Stocker Classification. (May 2023) - Dehner, Louis P.; Schultz, Kris Ann P.; Hill, D. Ashley
Congenital cystic pulmonary lesions (CCPLs) are represented by the following entities: congenital pulmonary airway malformation (CPAM), formerly congenital cystic adenomatoid malformation, extra- and intralobar sequestration (EIS), congenital lobar emphysema (overexpansion), and bronchogenic cyst. The developmental model of CPAM histogenesis by Stocker proposed perturbations designated as CPAM type 0 to type 4 without known or specific pathogenetic mechanisms along the airway from the bronchus to the alveolus. This review highlights mutational events either at the somatic level in KRAS (CPAM types 1 and possibly 3) or germline variants in congenital acinar dysplasia, formerly CPAM type 0, and pleuropulmonary blastoma (PPB), type I, formerly CPAM type 4. The potential for overt malignant progression exists in the case of PPB type I and CPAM type 1 in some cases to well-differentiated mucinous adenocarcinoma. On the other hand, CPAM type 2 is an acquired lesion resulting from interruption in lung development secondary to bronchial atresia. The latter is also regarded as the etiology of EIS whose pathologic features are similar, if not identical, to CPAM type 2. These observations have provided important insights into the pathogenetic mechanisms in the development of the CPAMs since the Stocker classification.